INHIBITION IN SPEAKING PERFORMANCE - Isna Humaera (Langkawi: Journal of The Association for Arabic and English, 2015)
The most common problem encountered by the learner in the languageacquisition process is learner inhibition. Inhibition refers to a temperamentaltendency to display wariness, fearfulness, or restrain in response tounfamiliar people, objects, and situations. There are some factors that causeinhibition, such as lack of motivation, shyness, self-confidence, self-esteem,and language ego. There are also levels of inhibition, it refers to kinds ofinhibition and caused of inhibition itself. Teacher can support their studentsto reduce their inhibition effect by many ways, one of them by creating goodclassroom management including establishing good rapport between teacherand learners.Keywords: Inhibition, Speaking Performance.